THE IMPACT OF SINTERING PROMOTER OXIDES ON MAGNESIA-DOPED ZIRCONIA CRYSTALS SYNTHESIZED BY SOL SPRAY PYROLYSIS PROCESS - Durrani, S. K.; Hussain, S. Z.; Arif, M.; Rehman, S.; Qazi, F.; Ahmad, N.; Mohammad, B. (The Nucleus, 2011)
Homogeneous crystalline 11mol.%magnesia doped partially stabilized zirconia (Mg-PSZ) and ZrO2 ceramics with and without addition of sintering promoter oxides such as CuO, MnO2 and CuO-MnO2 were synthesized by hydrothermal treatment of zirconium and magnesium salts using sol spray process. The spray dried ZrO2 and Mg-PSZ powders were calcined at 900o C and sintered upto 1200o C for 4 h. The relative density (~93% of theoretical) was achieved at 1100o C. The impact of sintering promoter oxides like 0.5mol % CuO, 0.5mol%MnO2 and 0.5mol%CuO-MnO2 on phase, microstructure development, texture properties (porosity, surface area, particle size distribution) and on the densification behavior of dense Mg-PSZ ceramic were examined. Sinterability of Mg-PSZ ceramic powder was found to depend upon the stoichiometric concentration of mixed salt solutions, flow rate of carrier gas and sintering promoter oxides. It was observed that both the Cu and Mn oxides are very effective as sintering aids. The small addition of sintering aid oxides, 0.5mol%CuO and 0.5mol%MnO2 reduced sintering temperature (by 150-200o C) and promoted densification rate of Mg-PSZ with respect to the mixed CuO-MnO2 addition. Addition of CuO enhanced the relative density and MnO2 decreased the relative densities. However, the addition of mixed CuO-MnO2 has an insignificant effect on the sintered density. The cubic structure Mg0.2Zr0.8O1.8 was detected by X-ray diffraction. The scanning electron microscope analysis revealed that sintering aid oxides CuO and MnO2 distorted surface morphology of MgPSZ nanocrystals rounded into dumb-belled shape with diameter of > 500nm.